Kajian Kinerja Pelayanan Operasional Pelabuhan Tanjung Perak Surabaya - Hartini, Citra Vidya; Wicaksono2, Achmad; Anwar, M. Ruslin (Jurnal Tata Kota dan Daerah, 2014)
Recently, the importance of ports, which was merely emphazied as storage, has shifted to as a connector to different transportation modes. Thus, it is essential for ports to adapt with a cheap, efficient, and effective transportation system. Efficiency and Effectiveness relate closely with port performance. The study location, the port of Tanjung Perak in Surabaya, is one significant support for the East Java Province’s economy. The aims of the study were to investigate its operational service level, to estimate its operational service level in the future, and to build better comprehension on the determining factors that lead to its operational service level. In this research, the performance evaluation will be measured based upon the General Directorate of Sea Transportation Decree No UM.002/38/18/DJPL-11 about Performance Standard of Port Operational Service (SKPOP). The methods used were correlation regression and IPA (Importance – Performance Analysis). Results showed that the port’s 2013 overall operational service performance has met SKPOP 2011 standards. The port’s waiting time performance was estimated to be over 2 hours in 2016, and raising to over 4.5 hours in 2020. Meanwhile, approach time performance in 2016 was predicted to be more than 7 hours. Moreover, the port’s berth occupancy ratio performance in 2016 was predicted to be above 80 %, shed occupancy ratio performance in 2016 is predicted to have above 70%. Finally, the study found that the determinig factors to Tanjung Perak Port’s operationa service level performance were the number and condition of tug and pilot boats, the availability and number of warehouse/storage yard, loading and unloading facilities, and the condition for road infrastructure. Keywords: IPA, port performance, Tanjung Perak Port, regression.